Pacbio Sequencing of PLC/PRF/5 Cell Line and Clearance of HBV Integration Through CRISPR/Cas-9 System - Chen, Chia-Chen; Guan, Guiwen; Qi, Xuewei; Abulaiti, Abudurexiti; Zhang, Ting; Liu, Jia; Lu, Fengmin; Chen, Xiangmei (Frontiers in Molecular Biosciences, 2021)
The integration of HBV DNA is one of the carcinogenic mechanisms of HBV, and the clearance of HBV integration in hepatocyte is of great significance to cure chronic HBV infection and thereby prevent the occurrence of HBV-related hepatocellular carcinoma (HCC). However, the traditional methods such as Alu-PCR were low sensitivity to detect HBV integration due to low the throughput. The second-generation sequencing can obtain a large amount of sequencing data, but the sequencing fragments are extremely short, so it cannot fully explore the characteristics of HBV integration. In this study, we used the third-generation sequencing technology owning advantages in sequencing length and sequencing depth to comprehensively analyze the HBV integration characteristics in PLC/PRF/5 cells. A total of 4,142,311 cleaning reads was obtained, with an average length of 18775.6 bp, of which 84 reads were fusion fragments of the HBV DNA and human genome. These fragments located in seven chromosomes, including chr3, chr4, chr8, chr12, chr13, chr16 and chr17. We observed lots of DNA rearrangement both in the human genome and HBV DNA fragments surrounding the HBV integration site, indicating the genome instability causing by HBV integration. By analyzing HBV integrated fragments of PLC/PRF/5 cells that can potentially express HBsAg, we selected three combinations of sgRNAs targeting the integrated fragments to knock out them by CRISPR/Cas9 system. We found that the sgRNA combinations could significantly decreased the level of HBsAg in the supernatant of PLC/PRF/5 cells, while accelerated cell proliferation. This study proved the effectiveness of third-generation sequencing to detect HBV integration, and provide a potential strategy to reach HBsAg clearance for chronic HBV infection patients, but the knock-out of HBV integration from human genome by CRISPR/Cas9 system may have a potential of carcinogenic risk.